Students’ Attitudes Towards Online Education: A Year into the COVID-19 Pandemic in Azerbaijan - Shahmarova, Aytan; Murshudova, Ramina (ADA University, 2023)
The unprecedented global lockdown during the COVID-19 pandemic led to “emergency remote teaching” (Pace et al. 2020; Hodges et al. 2020; Murshudova and Shahmarova et al, 2021) and the transition to online education. Azerbaijan initiated the compulsory change to online education, which brought various issues and challenges for students and teachers. The education system had to respond by relying on available resources. This research is based on similar research studies conducted in 2020, and 2021 of students’ attitudes towards online education, during the first online semester, and a year later after students had time to experience the process, observe the changes, and make final judgments about their preferences. In 2021, 77% of respondents from across 20 Azerbaijani Universities preferred the traditional learning model, while those who preferred online education had decreased by 13% from 2020. The importance of face-to-face communication in understanding subjects was the most popular argument for traditional learning. At the same time, the reduced cost of study was a top argument among those who expressed a willingness to continue learning online.
Keywords: Pandemic; Online education; transition; Azerbaijan